Effects of sodium tanshinone IIA sulfonate injection on pro-inflammatory cytokines, adhesion molecules and chemokines in Chinese patients with atherosclerosis and atherosclerotic cardiovascular disease: a meta-analysis of randomized controlled trials - Xie, Fan; Fu, Xiaoying; Li, Wenbo; Bao, Yujin; Chang, Feng; Lu, Yun; Lu, Yuqiong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundInflammation, as the basic pathogenic mechanism of atherosclerosis, promotes the development of atherosclerosis (AS) and atherosclerotic cardiovascular disease (ASCVD). In numerous experiments based on animal and cellular models, sodium tanshinone IIA sulfonate (STS) injection has been found to reduce the levels of pro-inflammatory cytokines, adhesion molecules, and chemokines in patients with AS and ASCVD, exerting an anti-inflammatory effect to treat the disease.ObjectivesThis study aimed to perform a meta-analysis of randomized controlled trials (RCTs) to quantify the effects of STS on pro-inflammatory cytokines, adhesion molecules, and chemokines in patients with AS and ASCVD.MethodsEight literature databases were searched from inception to January 2024, including PubMed, Web of Science, Cochrane Library, Ebsco, CNKI, VIP, WanFang Data, and ClinicalTrails.gov. Two reviewers independently screened articles and extracted data. The quality of the included studies was assessed using the Cochrane Risk Assessment Tool 2.0. Meta-analysis was performed using RevMan 5.4 software.ResultsOf the 2,698 publications screened, 42 studies were included, and the related trials involved 4,654 Chinese patients. The meta-analysis showed that STS significantly reduced the concentration level of pro-inflammatory cytokines interleukin 6 (IL-6) [standardized mean difference (SMD)=−1.50, 95%CI(−2.06, −0.95), p < 0.00001], tumor necrosis factor-α (TNF-α) [SMD = −2.55, 95%CI(−3.24, −1.86), p < 0.00001], and interleukin-1β (IL-1β) [SMD = −1.21, 95%CI(−2.41, −0.01), p < 0.0001], of adhesion molecules intercellular adhesion molecule-1 (ICAM-1) [SMD = −1.28, 95%CI(−1.55, −1.02), p < 0.00001] and p-selectin [SMD = −1.06, 95%CI(−1.46, −0.67), p < 0.00001], and of chemokines fractalkine [SMD = −1.32, 95%CI(−2.02, −0.61), p = 0.0003] and monocyte chemoattractant protein-1 (MCP-1) [SMD = −0.83, 95%CI(−1.11, −0.55), p < 0.00001] among patients with AS and ASCVD.ConclusionThe use of STS in patients with AS and ASCVD appeared to significantly decrease levels of pro-inflammatory cytokines, adhesion molecules, and chemokines.Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/], PROSPERO [CRD42024496960].